Wirosari Bus Terminal Performance Analysis Based on Facility Availability and Optimization Through Internet of Things (IoT) Technology - Irawan, Arie; Mudiyono, Rachmat; Pratikso, Pratikso (Journal of Engineering Science and Technology Management (JES-TM), 2025)
Wirosari Bus Terminal, a Type-C terminal located in Grobogan Regency, plays a crucial role in supporting rural mobility. However, underutilization and non-compliance with Indonesia's Minimum Service Standards (SPM) have significantly hampered its performance. This study evaluates the availability and quality of terminal facilities and proposes a technological optimization model based on the Internet of Things (IoT). Using a quantitative research design, 92 respondents including users, operators, and terminal staff were surveyed. The data were analyzed through multiple linear regression to determine the influence of facility availability (X₁) and technology perception (X₂) on terminal performance (Y). Results indicate that perceived facility availability is low (mean = 2.70), while technology acceptance is high (mean = 4.68). The regression model reveals that both variables significantly affect terminal performance (R² = 0.284, p < 0.05). This study concludes that enhancing physical infrastructure combined with IoT-based digital innovations such as real-time scheduling displays, electronic queuing, and sensor-based monitoring can significantly improve terminal functionality, user satisfaction, and operational transparency, especially in rural contexts.